The Role Of Mediators In Resolving Industrial Relations Disputes At The Manpower Office Of Makassar City - Madaniah Noer; Herman H; Muhammad Irvan Nur' Iva; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2026)
This study aims to analyze the role of mediators in resolving industrial relations disputes at the Makassar City Manpower Office using Ralph Linton’s Role Theory (1936), which emphasizes four key dimensions: role expectation, role performance, role conflict, and role clarity. The research employs a qualitative descriptive approach to obtain an in-depth understanding of mediator performance and institutional practices in dispute resolution processes. Data were collected through field observations, semi-structured interviews with mediators and relevant stakeholders, as well as document analysis of official dispute records and applicable regulatory frameworks. Data analysis was conducted using qualitative techniques, including data reduction, data display, and conclusion drawing. The findings indicate that mediator effectiveness is strongly influenced by the alignment between stakeholder expectations and actual role performance. Mediators are required not only to understand their formal duties and authority, but also to demonstrate professionalism, neutrality, and effective communication skills when facilitating negotiations between employers and workers. Role conflict mainly arises from institutional constraints, high workloads, and divergent interests among disputing parties, which can hinder the mediation process. Nevertheless, clear legal frameworks, standard operating procedures, and institutional support contribute significantly to maintaining role clarity and reducing role conflict. Overall, the study concludes that the integration of role expectation, role performance, effective management of role conflict, and role clarity enables mediators to perform their functions more professionally and effectively. Strengthening these dimensions is essential for sustainable governance.